2020
DOI: 10.3389/fnhum.2020.569010
|View full text |Cite
|
Sign up to set email alerts
|

Does Cardiorespiratory Fitness Influence the Effect of Acute Aerobic Exercise on Executive Function?

Abstract: Background The beneficial effects of acute exercise on executive function have been well-documented, but the influence of cardiorespiratory fitness on this effect requires further investigations, especially using imaging technique. This study aimed to examine the effects of cardiorespiratory fitness on acute exercise-induced changes on behavioral performance and on functional brain activation. Method Based on their cardiorespiratory fitness level, 62 participants ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
1
15
0
2
Order By: Relevance
“…In addition, a linear relationship was observed in the conditional effect output from the Johnson-Neyman technique indicating executive functioning performance increased as aerobic fitness increased. These findings support the potential influence of high levels of aerobic fitness following acute physical activity on executive functioning, however additional research is needed given inconsistencies within the literature (42,55,56,(58)(59)(60)(61)(62).…”
Section: Moderating Effects Of Physical Fitnesssupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, a linear relationship was observed in the conditional effect output from the Johnson-Neyman technique indicating executive functioning performance increased as aerobic fitness increased. These findings support the potential influence of high levels of aerobic fitness following acute physical activity on executive functioning, however additional research is needed given inconsistencies within the literature (42,55,56,(58)(59)(60)(61)(62).…”
Section: Moderating Effects Of Physical Fitnesssupporting
confidence: 59%
“…However, these findings were strictly limited to acute aerobic exercise performed at a moderate intensity. More recent experimental evidence continues to remain mixed across aerobic fitness levels, exercise intensities, age groups, and measures of executive functioning [i.e., (59)(60)(61)(62)] suggesting future research is warranted to further elucidate this complex relationship.…”
Section: Physical Fitness Executive Functioning and Acute Exercisementioning
confidence: 99%
“…As these regions are closely implicated in the modulation of emotions [21,48] and cognitive processes [49], functional changes in these regions may mediate many psychological benefits derived from regular exercise practice as well as exercise motivation and habits. In line with this, functional imaging studies have consistently reported associations between various indices of fitness such as VO 2peak or blood lactate curve and executive functions in lateral fronto-parietal and anterior cingulate cortices [5660]. Additionally, temporal regions have been suggested to play a role in regular exercise induced mood improvements [61], and insula and parietal cortex have shown altered reward processing in response to regular exercise training [62].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, environmental influencing factors (e.g., climatic and geographic conditions) and the actual state of the level of psychophysiological capacity (including abilities like cardiorespiratory fitness/performance level) should also be considered to compare the effects of acute physical exercise regarding interindividual response variability Herold et al, 2019;Gronwald et al, 2020b). For example, it has been observed that the effects of acute physical exercises on cognitive performance (Chang et al, 2012;Oberste et al, 2019) or functional brain activation patterns (Li et al, 2019;Ludyga et al, 2019;Cui et al, 2020) are modulated by the level of cardiorespiratory fitness or by regular physical activity level.…”
Section: Modifiable Non-exercise-related Factorsmentioning
confidence: 99%